The levels of oxytocin and oxyntomodulin, adiposity and blood indices in pharmacotherapy naive diabetic and non-diabetic patients with metabolic syndrome - Naserallah, RIHAM; Kasabri, Violet; AKOUR, AMAL; NAFFA, RANDA; BUSTANJI, YASSER; KHAWAJA, NAHLA (Jordan Journal of Pharmaceutical Sciences, 2018)
Aims: Our study aimed to investigate the correlation between plasma peptide hormones; oxytocin (OXT) and oxyntomodulin (OXM); as well as conicity index (CI), waist circumference (WC), waist circumference to hip circumference (WHR) ratio, red cell distribution width (RDW_CV%), mean platelet volume (MPV; fL) and TG\HDL-C ratio in metabolic syndrome (MetS) and Type-2 diabetes mellitus (T2DM) patients. Methods: In a cross-sectional design, 30 normoglycemic lean subjects (control), 30 MetS and 29 MetS-Pre/T2DM subjects were enrolled. Enzyme-Linked Immunosorbent Assay (ELISA) was used to measure plasma OXT and OXM. The correlations among these metabolic-biomarkers as well as patients’ adiposity and hematological indices were examined.Results: Median circulating levels of OXT (pg/ml) were lower in MetS and MetS-Pre/T2DM compared to control group ((median IQR) (MetS 1975.4and MetS-pre/T2DM 1403 vs. control 4176.6) , p=0.009 and p=0.001, respectively). Conversely median OXM (ng/mL) concentrations lacked any inter-group substantial variations (63023.6 (124670.05-13246.675); for the total study pool of recruits). Neither biomarker was described as substantially different in MetS vs. MetS-pre/T2DM (p>0.05).Principally in both MetS and MetS-pre/T2DM groups; CI, TG\HDL-C ratio, WC/HC ratio and RDW-CV% were described as markedly higher (p< 0.001) vs. controls’. Median MPV in MetS-pre/T2DM (but not in the nondiabetic MetS group’s) was significantly higher vs. controls’ MPV. However, all above MetS-related indices were not ascribed any statistically pronounced variations in MetS vs. MetS-pre/T2DM groups.Conclusions: In both MetS and MetS-pre/T2DM patients; OXT circulating concentrations were substantially decreased compared to lean controls while there were not any significant variations in OXM levels between three groups.